A 1, 2‐Dioxetane‐Based Chemiluminescent Probe for Highly Selective and Sensitive Detection of Superoxide Anions in Vitro and in Vivo. Issue 4 (5th April 2022) - Gong, Yuanyuan; Yang, Mingyan; Lv, Jiajia; Li, Hongyu; Gao, Jie; Yuan, Zeli
Abstract: Superoxide anion (O2 .− ), a short‐lived, highly active reactive oxygen species, participates in many physiological processes. This work reports the design of a chemiluminescent probe (CLO ) based on 1, 2‐dioxetane‐phenol with a selective and sensitive response to O2 .− . The CLO consisted of a 1, 2‐dioxetane‐phenol as a chemiluminophore core bearing a trifluoromethanesulfonate (Tf) moiety and methyl acrylate group. Upon reacting with O2 .−, the Tf was specifically cleaved from the CLO, resulting in chemiluminescence generation. The CLO emits chemiluminescence at 450–650 nm (λmax =540 nm), representing visible and red chemiluminescent molecules, responsive to O2 .− . The CLO processes high sensitivity (Limit of detection=66 nM) and selectivity for O2 .− with and has been applied to track O2 .− fluctuations in living cells and animals. In addition, CLO successfully detected and visualized O2 .− ‐related biochemical processes, making it promising as an important imaging tool for studying redox in biology and medicine. Abstract : CLO responds specifically in the presence of O2 . − to deprotect the trifluoromethanesulfonate group, which releases a chemiluminescent signal. CLO possesses high sensitivity and selectivity for O2 . − and has been successfully applied to track O2 . − fluctuations in living cells and animals. This study makes CLO promising as an imaging tool for studying redox systems in biology and medicine.